Analisis Pengaruh Kualitas Produk, Harga dan Celebrity Endorser Terhadap Keputusan Pembelian Skincare Ms Glow (Studi Pada Pengguna MS Glow di Kota Binjai) - Akhira Habrina Tarigan; Onan Marakali Siregar (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
One of the rapidly growing industries today is beauty products, beauty products including skincare products that can increase the confidence of its users. Therefore, In order to pique consumers' interest in purchasing their goods, businesses need to be able to compete in several markets. This research is to ascertain how the MS Glow skincare buying choice in Binjai City would be partly and concurrently influenced by product quality, price, and celebrity endorser. In this study, an associative method to quantitative research was used. One hundred MS Glow skincare consumers in Binjai City made up the study's population. Purposive sampling, which is non-probability sampling, was used in this investigation. The findings demonstrated that the choice to buy MS Glow skincare in Binjai City was significantly influenced by the product's quality, price, and celebrity endorsers, both partly and concurrently. With a R value of 0.583, the detemination coefficient test reveals a rather tight correlation between the three variables of product quality, price, and celebrity endorser. It is also known, based on the Adjusted R Square value, that factors influencing celebrity endorsers, prices, and product quality contribute 32.0% of the variables that impact purchase decisions, with the remaining 68.0% being influenced by factors beyond the scope of this research.